2015
DOI: 10.1371/journal.pone.0140177
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Early Maladaptive Schemas in the Relation between Co-Rumination and Depression in Young Adults

Abstract: Research on co-rumination has investigated its relationship with internalizing symptoms, but few studies have addressed underlying maladaptive cognitive-affective processes that may play an important role in the maintenance of this relation. This study examines if Young’s schema domains mediate the relation between co-rumination and depression in a community sample of non-clinical young adults. Participants completed the Co-Rumination Questionnaire, Young Schema Questionnaire-L3, and Teate Depression Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 54 publications
2
41
0
1
Order By: Relevance
“…In general, there is limited literature about the influence of gender in early maladaptive schemas (Balsamo, Carlucci, Sergi, Klein Murdock, & Saggino, 2015;El-Gilany, El-Bilsha, & Ibrahim, 2013;Peixoto & Nobre, 2015). Similarly, these findings are consistent with the predictions of theories in the fields of psychosocial development and cultural schemas (Timmerman & Emmelkamp, 2006;Erikson, 1963;Malcolm & Sharifian, 2002;Palmer, 1996;Piaget, 1970;Strauss & Quinn, 1997;Wills & Sanders, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In general, there is limited literature about the influence of gender in early maladaptive schemas (Balsamo, Carlucci, Sergi, Klein Murdock, & Saggino, 2015;El-Gilany, El-Bilsha, & Ibrahim, 2013;Peixoto & Nobre, 2015). Similarly, these findings are consistent with the predictions of theories in the fields of psychosocial development and cultural schemas (Timmerman & Emmelkamp, 2006;Erikson, 1963;Malcolm & Sharifian, 2002;Palmer, 1996;Piaget, 1970;Strauss & Quinn, 1997;Wills & Sanders, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…In this field, a few studies showed significant gender differences in EMSs. These studies indicated that women have a relatively high rate of maladaptive schemas (Balsamo, Carlucci, Sergi, Klein Murdock & Saggino, 2015;El-Gilany, El-Bilsha, & Ibrahim, 2013;Peixoto & Nobre, 2015). This research is essential because EMSs are mental structures which allow people to stock up perceptual and conceptual information about their culture, and also help people to interpret cultural experiences within specific lenses in social contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Balsamo reported a relationship between depression and EMSs. Nonetheless, he emphasized the role of coping style [14]. According to cognitive theories, these findings can be attributed to the fact that EMSs are related to negative deeply-rooted beliefs about the self, others, and the world.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that there is a relationship between depression and EMSs [13]. Nonetheless, some studies have not found a relationship between EMSs and depression [14]. The review of related literature shows that, there is a lack of research regarding the relationship between PPD and EMSs.…”
Section: Introductionmentioning
confidence: 99%
“…As with all research, some limitations of our study have to be observed. First, because this study can be considered as an observational cross‐sectional rather than a true experimental one, no causal relationships among variables may be inferred (Balsamo, Carlucci, Sergi, Murdock, & Saggino, ). Second, measures of the variables were exclusively based on self‐report instruments and relied solely on one informant.…”
Section: Discussionmentioning
confidence: 99%